SAMPA: A free software tool for skin and membrane permeation data analysis - Bezrouk, Aleš; Fiala, Zdeněk; Kotingová, Lenka; Krulichová, Iva Selke; Kopečná, Monika; Vávrová, Kateřina (Toxicology in vitro, 2017)
Skin and membrane permeation experiments comprise an important step in the development of a transdermal or topical formulation or toxicological risk assessment. The standard method for analyzing these data relies on the linear part of a permeation profile. However, it is difficult to objectively determine when the profile becomes linear, or the experiment duration may be insufficient to reach a maximum or steady state. Here, we present a software tool for Skin And Membrane Permeation data Analysis, SAMPA, that is easy to use and overcomes several of these difficulties. The SAMPA method and software have been validated on in vitro and in vivo permeation data on human, pig and rat skin and model stratum corneum lipid membranes using compounds that range from highly lipophilic polycyclic aromatic hydrocarbons to highly hydrophilic antiviral drug, with and without two permeation enhancers. The SAMPA performance was compared with the standard method using a linear part of the permeation profile and a complex mathematical model. SAMPA is a user-friendly, open-source software tool for analyzing the data obtained from skin and membrane permeation experiments. It runs on a Microsoft Windows platform and is freely available as a Supporting file to this article.
Keywords: Skin Absorption; Rats; kožní absorpce; Flux; Transdermal drug delivery; krysa rodu Rattus; Data analysis; Swine; Skin permeability; léčivé přípravky; zvířata; Humans; Software; Skin; Pharmaceutical Preparations; Cell Membrane Permeability; prasata; software; permeabilita buněčné membrány; kůže; lidé; Animals